The application of DNA markers in population genetics of mosquitoes: a comprehensive review - Wei, Yong; Wei, Yuanhuan; He, Song (Frontiers in Insect Science, 2026)
Mosquitoes are major vectors of pathogens causing diseases such as dengue, malaria, and Japanese encephalitis, imposing significant global public health and economic burdens. Traditional morphological approaches for mosquito research are limited by the reliance on specialized taxonomic expertise, the inability to distinguish cryptic species or immature life stages, and the susceptibility to environmental factors. DNA markers have emerged as indispensable tools to address these limitations. This review systematically summarizes the characteristics and applications of important DNA markers in mosquito population genetics research, covering core areas such as species identification, evolutionary and phylogenetic studies, invasion history and population genetic structure analysis, genetic mapping and quantitative trait locus (QTL) analysis, and genome-wide association studies (GWAS). This review highlights the pivotal role of DNA markers in advancing the understanding of mosquito biology and supporting the development of effective strategies for mitigating mosquito-borne diseases.